Nourish me home : 125 soul-sustaining, elemental recipes - Burns, Cortney (Chronicle Books, 2020)
"Renowned chef and tastemaker Cortney Burns left the streets of San Francisco for the rural mountains and gnarled history of New England. She learned the ways and flavors of her new home through its people, gardens, forests, and dramatic seasons, and translated all of it into her famous cooking. In this groundbreaking new project, she tells the story of her personal journey and how any cook can work their spirituality and sense of place into what they create. This is elemental home cooking, with 125 recipes for those looking to build their repertoire of nourishing, delicious foods. Organized like no other cookbook, here each chapter focuses on a different element. Fire is all about roasting meats, vegetables shine in Earth, Water features soups and stews, the magic of baking is revealed in Air, and Aether offers imaginative, healthful takes on preserves. This collection comes in a sensually compelling, foil-stamped package, with 100 vibrant photographs and 50 hand-drawn illustrations of beautiful feathers, flowers, and medicinal plants"--